Physical Rehabilitation of Adolescents with Minor Structural Cardiac Abnormalities - Sergiy Vozniy; Yuriy Romaskevych; Petro Godlevskiy (Lesya Ukrainka Volyn National University, 2018)
Topicality. The article shows the method of physical rehabilitation of adolescents with minor structural cardiac abnormalities. Minor structural cardiac abnormalities  is a large group of cardiovascular anomalies, characterized by the presence of a variety of anatomical and morphological deviations from the norm of the heart structures that make up the undifferentiated connective tissue dysplasia. The most common cardiac manifestations of connective tissue dysplasia syndrome are mitral valve prolapse and abnormal chords of the left ventricle of the heart. Diagnosis of this pathology in adolescents has significantly increased with the development of ultrasound examination of the heart, while the technique of physical rehabilitation has not been sufficiently developed to date. The aim of the research is to study the effect of rationally dose-related physical exertion on the severity of the main symptoms of the disease and the physical condition of adolescents with minor structural cardiac abnormalities. Methods of Work. Questionnaire to identify a subjective assessment of the severity of the main symptoms of the disease, the definition of exercise tolerance and the index of the physical state of adolescents according to the methodology of Professor O. Shchepin. Results of Work. Physical rehabilitation was carried out in three stages, general strengthening exercises of aerobic and anaerobic power, exercises on simulators, sports-applied exercises, outdoor games, respiratory gymnastics, special exercises to increase the stability of the vestibular apparatus, orthostatic firmness, the formation of correct posture and flatfoot prevention. The loads were dosed individually, taking into account the results of determining the tolerance to physical activity. Conclusion. As a result of the rehabilitation actions the general conditions of the adolescents were improved, the symptoms of the disease began to disturb them less often and disappear. The index of physical condition increased for boys from an average of 0,52 ± 0,007 to an above average of 0,70 ± 0,001, and for girls from the lower limit of the average 0,51 ± 0,006 to the upper one and was 0,69 ± 0,004.